Burnout in nurses working with cardiac patients - María Josefa Díaz-Muñoz Crespo (Fundación para el Desarrollo de la Enfermería, 2005)
The burnout syndrome has been described as a frequent job-related health problem in nurses. This syndrome is characterized by emotional fatigue, low personal accomplishment and depersonalization. Its prevalence has not been specifically explored in nurses attending cardiac patients. We designed a prevalence study including nursing staff in a cardiologic hospital (ward and ICU). In addition to sociolaboral data, information regarding the dimensions of the Maslach Burnout Inventory were recorded. Only 50% of the 52 elegible nurses and allied professionals answered the questionnaires: 22 females, median age 41 years, most of them with couple (58%) and children (61%); mean of work experience 15 years. 8% of the subjects showed high rates of emotional fatigue, despersonalization (31%)and low grade of personal accomplishment (38,5%). No subjects met criteria for burnout. Emotional fatigue was more frequent in females, singles, with no children, allied and older professionals. Workers with no children and allied professionals showed higher rates of despersonalization. The personal accomplishment was higher in married and ICU personnel. The observed rate of burnout was low, although only 8% showed normal rates in all Maslach Burnout Inventory dimensions. The personal accomplishment dimension was the one more affected.